Middle meningeal artery: Gateway for effective transarterial Onyx embolization of dural arteriovenous fistulas. Issue 6 (7th June 2016) - Griessenauer, Christoph J.; He, Lucy; Salem, Mohamed; Chua, Michelle H.; Ogilvy, Christopher S.; Thomas, Ajith J.
Abstract : Curative transarterial embolization of noncavernous sinus dural arteriovenous fistulas (dAVFs) is challenging. We sought to evaluate the role of the middle meningeal artery (MMA) in endovascular treatment of these lesions. We performed a retrospective cohort study on patients who underwent transarterial Onyx embolization of a noncavernous sinus dAVFs with contribution from the MMA at a major academic institution in the United States from January 2009 to January 2015. Twenty consecutive patients who underwent transarterial Onyx embolization of a noncavernous sinus dAVF were identified. One patient was excluded as there was no MMA contribution to the dAVF. All of the remaining 19 patients (61.3 ± 13.8 years of age) underwent transarterial embolization through the MMA. Six patients (31.6%) presented with intraparenchymal or subarachnoid hemorrhage from the dAVF. The overall angiographic cure rate was 73.7% upon last follow up. In 71.4% of successfully treated patients transarterial embolization of the MMA alone was sufficient to achieve angiographic cure. When robust MMA supply was present, MMA embolization resulted in angiographic cure even after embolization of other arterial feeders had failed in 92.9% of patients. A robust contribution of the MMA to the fistula was the single most important predictor for successful embolization ( P = 0.00129). We attribute our findings to the fairly straight, non‐tortuous course of the MMA that facilitates microcatheter access, navigation, and Onyx penetration. Noncavernous sinus dAVF can be successfully embolized with transarterial Onyx through the MMA, as long as supply is robust. A transvenous approach is rarely necessary. Clin. Anat. 29:718–728, 2016. © 2016 Wiley Periodicals, Inc.